Peningkatan kompetensi guru bahasa Jerman melalui pelatihan project based learning berbasis Sustainable Development Goals (SDGs) - Isti Haryati; Iman Santoso; Sudarmaji Sudarmaji; Retna Endah Sri Mulyati; Diyan Fatimatuz Zahro (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Project-Based Learning (PjBL) is an effective teaching method for empowering learners of the German language. However, not all teachers fully understand how to integrate PjBL within German language learning and connect it to global issues. Therefore, the objectives of this community service activity are: (1) to provide up-to-date knowledge for German language teachers about the PjBL method in German language teaching, (2) to train teachers on how to integrate Sustainable Development Goals (SDGs) through the PjBL method in German language instruction. The activities conducted in this community service program consist of three stages: (1) Explanation of the urgency of SDGs-based PjBL in German language teaching, explanation of SDGs in German language learning, explanation of PjBL in German language teaching, and (2) Drafting SDGs-based PjBL lesson plans by German language teachers, (3) Online presentation of the SDGs-based PjBL lesson plan drafts by German language teachers. The outcomes achieved from this community service program are as follows: (1) There were 19 training participants offline and 14 participants online, (2) the participating teachers expanded their understanding of PjBL) and SDGs within the context of teaching the German language, and (3) teachers enhanced their abilities to design and incorporate SDGs-oriented PjBL approaches into German language instruction.